A COMPREHENSIVE STRATEGIC PARTNERSHIP: SYNCHRONIZING CHINA’S BELT AND ROAD INITIATIVE (BRI) ON RUSSIA’S EURASIA ECONOMIC UNION (EAEU) - Hendra Manurung (Sociae Polites, 2019)
This research attempts to enrich debate by addressing the relationship of the China’s Belt and Road Initiative with the Russia’s Eurasian Economic Union (EAEU). Currently, it is a common phenomenon where a regional economic grouping bringing together several of China’s important BRI partners including Russia and Central Asian countries. Since 2013, China’s Belt and Road Initiative (BRI) initiated, developed, and has been promptly placed among the top priorities of China’s foreign policy consideration in Beijing. One of the BRI’s cooperation priorities is unimpeded trade, which implies the improvement of the investment and trade facilitation and removal of the recurrent investment and trade barriers. Despite its apparent flexibility and openness to embracing existing regional and multilateral platforms, there has been little debate on the compatibility of the BRI objectives with the existing economic integration projects. Thus, it raises a question on how these two initiatives go along smoothly, why it needs to be developed and how it will be develop. Meanwhile, it exists also the U.S-China trade war which has been going intensively for two years since 2017. It addresses the current progress in bridging the two major economic projects and outlines the strategic decision-making priority directions for further coordination between these two global major powers.